If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6x + -4) + 3(7 + -3x) + -2(4x + 2) = -2 Reorder the terms: 3(-4 + 6x) + 3(7 + -3x) + -2(4x + 2) = -2 (-4 * 3 + 6x * 3) + 3(7 + -3x) + -2(4x + 2) = -2 (-12 + 18x) + 3(7 + -3x) + -2(4x + 2) = -2 -12 + 18x + (7 * 3 + -3x * 3) + -2(4x + 2) = -2 -12 + 18x + (21 + -9x) + -2(4x + 2) = -2 Reorder the terms: -12 + 18x + 21 + -9x + -2(2 + 4x) = -2 -12 + 18x + 21 + -9x + (2 * -2 + 4x * -2) = -2 -12 + 18x + 21 + -9x + (-4 + -8x) = -2 Reorder the terms: -12 + 21 + -4 + 18x + -9x + -8x = -2 Combine like terms: -12 + 21 = 9 9 + -4 + 18x + -9x + -8x = -2 Combine like terms: 9 + -4 = 5 5 + 18x + -9x + -8x = -2 Combine like terms: 18x + -9x = 9x 5 + 9x + -8x = -2 Combine like terms: 9x + -8x = 1x 5 + 1x = -2 Solving 5 + 1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 1x = -2 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = -2 + -5 1x = -2 + -5 Combine like terms: -2 + -5 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| .3x^2-1.8-.3=0 | | (x-7)(3x+2)= | | 2(x+1)+2(x+1)=5 | | 3.3q-3.2-5.1q=0.8q-3.2 | | 6y+9=5y-5 | | x+ax+b= | | 7.1t-8=7.1t-8 | | 3i(7i)= | | 13y+39=11y+15 | | x^2+x(1-6q+q^2)+(-4q^3+8q^2-4q)=0 | | -5(2t-4)+6t=3t-5 | | 12-12x=23x | | y=4-3x+3 | | -4x^4(8-8x+3x^4)=0 | | 3(4z-8)-2= | | 10.50a+82=2017.50 | | 27=-9x-3y | | 14+0.1(x-300)=32.80 | | 3a-3b+3c=0 | | 5a+3b+2c=3a-3b+3c | | -3(4t-2)+5t=4t-4 | | 3a-3b+3b=0 | | z^2-2y+7z^2-2y+6z^2-22z^3+2-16y+2z^3= | | 5a+3b+2c=3a-3b+3b | | 9x-1=9(x-3) | | 5a+3b+2c=3a | | 14-7+12-18= | | 14ab-7ab+12b-18a+bc= | | 7x^4-14x^4+3x^3= | | 86-(3x+16)=3(x+7)+x | | 2(2m-2)-21= | | y=-1.04x+50.3 |